The Perceptions of Social Media Usage and Their Correlates among the University Student Population - Subedi, Chudamani; Upadhyay , Thakur Prasad (Asian Journal of Population Sciences, 2026)
The widespread use of social media (SM), especially by college students, in a developing country like Nepal, has resulted in various negative and, to some extent, positive side effects. The aim of this study is guided by the idea that people behave based on their perception of reality, not based on reality itself. An in-depth understanding of the perception of SM usage and its correlates is, therefore, of vital importance for better use of it in the days to come. A descriptive quantitative research design was followed, where 163 student samples were collected through a field survey for the study. Perceptions on five different dimensions of SM use and their correlates are analysed. The findings show that the majority of students agree that SM helps enhance social connectedness and information sharing aspects, while a significant proportion perceives negative reactions to SM use by family members and negative impacts of SM use. Students’ perceptions of SM use are not significantly different between males and females. Mother’s education is significantly positively correlated with the perception of negative health effects. The negative family reaction toward the use of SM is highest among teens, suggesting that parents are more concerned about the excessive use of SM by their kids. Science and management student groups regard highly of importance of SM in socializing. These findings suggest that parents can play an important role in reducing the SM time, preventing negative consequences. Socialisation and sharing of information dimensions can be important contributions of SM toward a better lifestyle in the current digital era.